Biological Restoration of a Fractured Anterior Tooth with the Use of Dentine Pin (Biopins) - Lilian Capanema Nogueira; Karine Taís Aguiar Tavano; Nayara Kelly Lyrio Ferraz; José Cristiano Ramos Glória; Adriana Maria Botelho (Case Reports in Dentistry)
This case study describes the esthetic and functional reconstruction of a fractured maxillary central incisor. Due to the requirement for additional retention, treatment was performed using the homogenous technique of biological restoration associated with cementation of posts made from human dentin (biopins). This type of treatment is a new alternative to conventional techniques and favors the dental esthetic and function, as well as biocompatibility, and is an inexpensive procedure.